Differential Effects of Krill Oil and Fish Oil on the Hepatic Transcriptome in Mice - Burri, Lena; Berge, Kjetil; Wibrand, Karin; Berge, Rolf K.; Barger, Jamie L. (Frontiers in Genetics, 2011)
Dietary supplementation with ω-3 polyunsaturated fatty acids (ω-3 PUFAs), specifically the fatty acids docosahexaenoic acid (DHA; 22:6 ω-3) and eicosapentaenoic acid (EPA; 20:5 ω-3), is known to have beneficial health effects including improvements in glucose and lipid homeostasis and modulation of inflammation. To evaluate the efficacy of two different sources of ω-3 PUFAs, we performed gene expression profiling in the liver of mice fed diets supplemented with either fish oil (FO) or krill oil (KO). We found that ω-3 PUFA supplements derived from a phospholipid krill fraction (KO) downregulated the activity of pathways involved in hepatic glucose production as well as lipid and cholesterol synthesis. The data also suggested that KO-supplementation increases the activity of the mitochondrial respiratory chain. Surprisingly, an equimolar dose of EPA and DHA derived from FO modulated fewer pathways than a KO-supplemented diet and did not modulate key metabolic pathways regulated by KO, including glucose metabolism, lipid metabolism and the mitochondrial respiratory chain. Moreover, FO upregulated the cholesterol synthesis pathway, which was the opposite effect of krill-supplementation. Neither diet elicited changes in plasma levels of lipids, glucose, or insulin, probably because the mice used in this study were young and were fed a low-fat diet. Further studies of KO-supplementation using animal models of metabolic disorders and/or diets with a higher level of fat may be required to observe these effects.